Encounters with Jesus : uncover the ancient culture, discover hidden meanings - Burge, Gary M., 1952- (Grand Rapids, Mich. : Zondervan, 2010)
"What can you do, or think, or believe to make yourself 'untouchable' to Jesus? The answer, according to Gary M. Burge, is nothing. In this insightful, well-researched book, Burge examines Jesus' biblical encounters with everyday people and concludes, 'Nothing in our lives or situations will be an impediment to him all are welcome.' ... Do you sometimes feel like an 'untouchable'? Have you ever been ashamed to say, 'You don't know what I've done, how unethical I've been, how many bad decisions I've made, how many times I've shaken my fist at God'? If so, you're not alone. Thankfully, author Gary M. Burge has a message for you, and others like you: Jesus wants to encounter you, just as you are. When Burge re-examined Jesus' biblical encounters with people being careful to view them in their unique historical context he emerged with fresh, powerful insights about how Jesus interacted with people then, and still does today 'One of the more surprising features of Jesus ministry was his willingness to have personal encounters with people, ' he writes. 'In fact, what is unique about the gospels are the unexpected stories that detailed Jesus regular interruptions.' These 'interruptions' came in the form of people from all walks of life young, old, rich, poor, sick, healthy, riddled with sin, or saddled by self-righteousness. 'No situation or condition will impede Jesus approach, ' Burge writes. 'All are welcome.'"--Publisher description.
Encountering Jesus -- The woman with the hemorrhage (Matthew 9:18-26; Mark 5:21-43) -- Zacchaeus of Jericho (Luke 19:1-10) -- The centurion of Capernaum (Luke 7:1-10) -- A woman in Samaria (John 4:4-26) -- A Greek woman in Tyre (Matthew 15:21-28; Mark 7:24-30).
Includes bibliographical references (pages 126-127) and index.
Keywords: Jesus Christ -- Friends and associates